أثر تواتر الإفصاح على أداء صناديق الاستثمار ( دراسة تطبيقية على عينة من صناديق الاستثمار في سوق الكويت للأوراق المالية ) - دله, سام; الغصين, راغب; بركات, أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تختبر هذه الدراسة مدى أثر تواتر الإفصاح على أداء صناديق الاستثمار واختبار مدى الفائدة من اعتماد التقارير المالية للصناديق على الإفصاحات الدورية. وقد استخدم الباحث معامل التوافق غاما في هذه الدراسة بالتطبيق على أربعة صناديق من سوق الكويت للأوراق المالية خلال عامي 2012م-2013م أخذاً بالحسبان فيما إذا كانت الصناديق تقليدية أم إسلامية. وقد أشارت نتائج الدراسة بأنه لا يوجد فرق بين الإفصاحات الدورية على أداء صناديق الاستثمار الإسلامية في حين لاحظت الدراسة وجود فرق بين الإفصاحات الدورية على أداء صناديق الاستثمار التقليدية وخصوصاً الإفصاح نصف السنوي والسنوي، وقد اقترح الباحث تعديل المادة رقم ( 349 ) بخصوص إعداد قوائم مالية للصندوق بشكل ربع سنوي ليصبح نشر هذه التقارير بشكل نصف سنوي وسنوي وأن تتضمن تقارير الإفصاح مؤشرات الأداء (العائد، المخاطرة، شارب، ترينور، ) بالنسبة للصناديق التقليدية لأن ذكر هذه المؤشرات يشكل فرقاً وتأثيراً على صنع قرار المستثمر. This study examinesimpact of disclosure frequency on the performance of investment funds and examines the usefulness of the adoption of financial reports on the periodicaldisclosure.The researcher used standard Gamma on the application of four funds of the Kuwait Stock Exchange during 2012-2013,two of the funds are conventional and two are islamic.The results indicated that there is no relationship between the periodical disclosure and the performance of Islamic funds while the restudy is a relationship between periodical disclosure andperformance of the traditional Investment Funds especially the disclosure of the semi-annual and annual.The researcher suggests to modify the Article No.( 349 ) for the preparation of financial statements of the Fund on aquarterly basis so that the publication of these reports become as semi-annual and annual and the disclosure of these reports should includes performance indicators ( return, risk,Sharpe,treynor, ) for the traditional funds because disclosing these indicators makes a difference and an impact on the investor’sdecision making.